Analisis Strategi Optimalisasi Pembelajaran Muatan Lokal Keat Taubahan dalam Pembentukan Karakter Religius Siswa di MTs at Taubah Cimanggu - Urohmah, Annisa; Aniroh (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze optimization strategies, curriculum integration, and the impact of Keat Taubahan local content learning in shaping students' religious character at MTs At Taubah Cimanggu. This study uses a descriptive qualitative approach with a case study design. Data were obtained through in-depth interviews, participatory observation, and documentation studies, then analyzed through data reduction, thematic grouping, data presentation, and drawing and verifying conclusions. The results of the study show three main findings. First, learning optimization is carried out through the use of Interactive Flat Panel (IFP) and video assignments in the DUKLET private Facebook group to increase the engagement of digital generation students. Second, curriculum integration is realized through co-curricular activities of local history murals and learning religious practices in stages, including prayer readings, bilal, wirid, and tahlil. Third, learning contributes to the habit of independent worship at home and strengthening spiritual awareness through pilgrimages to the graves of local figures. The Personality Book serves as an instrument for monitoring the development of students' worship and memorization by involving the madrasah and parents. These findings indicate that character-based local content learning can be developed adaptively through the integration of technology, local history, religious habits, and continuous monitoring.